(untitled) (Olhar de Professor, 2012)
Media education as a fi eld in construction involves approaching the various areas of knowledge, their objects and transdisciplinary practices that are also part of an international movement.Considering media education as a fi eld, discipline, social practice and media-educational stance, the text discusses some conceptual and historical aspects of the trajectory of media education and its theoretical and methodological perspectives in educational practice and research. The plural identity of media education, its objectives and perspectives demonstrate study possibilities, research and intervention in educational and cultural practices. To contribute with this refl ection, the text indicates some challenges to media education in the context of digital culture.